Priporočilo Sveta o dostopu delavcev in samozaposlenih oseb do socialne zaščite ter slovenska pravna ureditev - Bagari, Sara (Delavci in delodajalci, 2020)
The article deals with the Council Recommendation on access to social protection for workers and the self-employed. The introductory presentation of the meaning, purpose, and legal nature of the Recommendation is followed by a content analysis. The Recommendation aims to encourage Member States to provide all workers (regardless of the type and duration of their employment relationship) and the self-employed with (i) formal coverage, (ii) effective coverage, (iii) adequacy of social protection, and (iv) transparency of social protection entitlements. In this context, the contribution also analyses the Slovenian legal system, highlighting its shortcomings and possibilities for improvement.
Keywords: delovna razmerja; delovno pravo; samozaposleni; samozaposlovanje; Slovenija; socialna varnost; socialna zaščita; socialno pravo